A bibliometric study on the adoption of mobile health: trends and future directions - Sakarji, Siti Rosnita; Othman, Abdul Kadir; Mohd Beta, Raja Mayang Delima; Narmaditya, Bagus Shandy (International Journal of Public Health Science (IJPHS), 2025)
This study presents a comprehensive overview of research on mobile health applications (mHealth apps) from 2013 to 2023. A total of 207 research papers from the Scopus database were analyzed. Based on keyword co-occurrences and co-authorship mapping, the paper identifies emerging trends and research patterns by using the VOSviewer software. Over the past ten years, there has been a discernible increase in the number of mHealth publications. However, a lack of attention has been given to the Asian context. It is anticipated that applications of mHealth will be observed in numerous health services given the high volume of citations obtained in this subject. The present review paper is assisted by the bibliometric approach and offers a rigorous analysis of journal papers on mHealth that have been published. The findings of the current work may serve as a foundation for further research in this discipline that focuses on bringing attention to the nature of the subject matter. This overview could be a central resource for researchers and practitioners looking for information that can help with cross-disciplinary projects by directing them to recognized peer-reviewed publications, journals, and networks.